Rice Production in India : Trend and Decomposition Analysis - Savadatti, Pushpa M. (Arthshastra Indian Journal of Economics & Research, 2018)
The present paper attempted to study the growth rates in area, production, and yield of rice crop in India during four sub periods, mainly pre - green revolution period : 1950 - 51 to 1964 - 65 ; green and post - green revolution period : 1965 - 66 to 1989 - 90 ; post reforms period: 1990 - 91 to 2016 - 17, and overall period : 1950 - 51 to 2016 - 17 based on time series data collected from RBI and CMIE databases. The techniques like coefficient of variation, compound growth rates (CGR), and decomposition analysis were used for the analysis. The results of descriptive statistics showed that mean area, production, and yield of rice crop exhibited an increasing trend during different sub-periods and it was highest during the post - reforms period. Area displayed more volatility during different periods of the study. CGR results showed significant growth in area during pre and post green revolution periods, but during the post reforms period, it was yield, which showed significant growth as compared to area. Decomposition analysis indicated that area effect in enhancing the rice production declined over a period of time, but that of yield effect increased. Since land is limited in supply, more emphasis should be given to yield enhancement in order to meet the increasing demand for rice in the future.